Denture stomatitis - Iba, Bemhemba; Falegbe, Rapheal Kehinde; Iortyom, Chile; Nwaohabuenyi, Thelma; Asa, Yomi Isaac; Ibeobi, Ada Cynthia; Dogoh, Aondover Festus (Orapuh Journal, 2021)
Denture stomatitis is the most occurring problem of denture wearers and presents in more than two-thirds of the patients wearing removable dentures with the prevalence rate increasing with age. The objective of this review was to present a succinct discussion on the prevalence, aetiology, classification, clinical features, and management of denture stomatitis based on conventional and recently published works of literature. To review denture stomatitis, a search was made in the databases and electronic search tools such as PubMed, SciELO, Google Scholar, ResearchGate, Medscape, and Web of Science for literature written in the English language and published from 2017 – 2021 only, using keywords, such as denture stomatitis, management of denture stomatitis, Candida albicans, antifungal, and oral candidiasis. The study revealed that the aetiology of denture stomatitis was not clearly defined though it was linked to multifactorial causes with local and systemic predisposing factors playing key roles in the occurrence of the condition. About 80-90% of denture stomatitis was associated with microorganisms. Particularly, yeast of the genus, Candida, was implicated as the causative organism. Comprehensive management involving good oral and denture hygiene together with antifungal therapy is effective in the rapid healing of the inflammatory lesions whereas, maintenance of good oral and denture hygiene, correction of denture faults, quitting of bad oral habits like smoking, and discouragement of denture wearing at night are very effective in preventing denture stomatitis.